Akilli telefonlar için geliştirilmiş hafif siklet veri gizleme uygulamasi - Gündüzalp, Veysel; Tuncer, Türker; Ulaş, Mustafa; Avci, Engin (Institute of Electrical and Electronics Engineers Inc., 2017)
Nowadays, the using of smartphones has expeditiously increased. The developing of information security applications for smartphones becomes important because of the fact that a clear majority of individuals informations accupy in smartphones. For this reason the developing of ligeweight information security applications becomes vitally important. In this study, a data-hiding schema that runs speedly and whose availability is high is suggested for smartphones. Data-hiding schema should be high capacity, speedy and safe is prioritised. © 2017 IEEE.
2017 International Artificial Intelligence and Data Processing Symposium, IDAP 2017 -- 16 September 2017 through 17 September 2017 -- Malatya -- 115012
Keywords: Image processing; Lightweight data hiding; Mobile security; Steganography